Plast-Shred Paper Composite - Hanis Azimah, Mohd Bokeri; Alida, Abdullah; Che Mohd Ruzaidi, Ghazali, Prof. Madya (Supervisor) (Universiti Teknologi MARA, Kedah, 2010)
Invention, Innovation & Design (IID Kedah 2010), 28th - 29th July 2010 organized by Research & Industrial Linkages Division, Universiti Teknologi MARA (UiTM), Kedah at SP Inn, Kedah.